Preaching for the rest of us : essentials for text-driven preaching - Gallaty, Robby, 1976-; Smith, Steven (B & H Academic, 2018)
Preaching for the Rest of Us serves as a starter's guide to text-driven preaching. Driven by the conviction that pastors hold the weighty and honorable responsibility of explaining Scripture to their congregations, Gallaty and Smith present a clear step-by-step process for re-presenting Scripture in compelling text-driven sermons.